Oligopolization of the Polish Pharmacy Market: Impacts and Regulatory Recommendations under the 'Pharmacy for Pharmacists 2.0' Act - Piekara, Agnieszka (Management and Administration Journal, 2025)
Over the past 15 years, the Polish pharmacy market has undergone an intensive process of ownership transformation, resulting in a decline in the number of independent pharmacies in favor of chain entities. The aim of this article is to identify and discuss the risks arising from the growing ownership concentration in the Polish pharmacy market and to justify the need for maintaining and strengthening regulations that protect its structure. Particular attention is given to the potential effects of reintroducing AdA 2.0. The article presents a review of literature and data, an analysis of the consequences of monopolization for various stakeholder groups (small businesses, patients, and the healthcare system), as well as recommendations for future legislative directions. The oligopolization and monopolization of the pharmacy market in Poland is not solely an economic issue – it constitutes a problem with multidimensional social, health, and state-level